2005
DOI: 10.1158/0008-5472.can-04-4407
|View full text |Cite
|
Sign up to set email alerts
|

Functional Epigenomics Identifies Genes Frequently Silenced in Prostate Cancer

Abstract: In many cases, silencing of gene expression by CpG methylation is causally involved in carcinogenesis. Furthermore, cancer-specific CpG methylation may serve as a tumor marker. In order to identify candidate genes for inactivation by CpG methylation in prostate cancer, the prostate cancer cell lines LNCaP, PC3, and Du-145 were treated with 5-aza-2V deoxycytidine and trichostatin A, which leads to reversion of epigenetic silencing. By microarray analysis of 18,400 individual transcripts, several hundred genes w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
223
0
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(249 citation statements)
references
References 47 publications
24
223
0
2
Order By: Relevance
“…Consistent with that idea, we have previously found that SFRP1 is methylated in several breast cancer cell lines (Suzuki et al, 2002), and two other groups recently reported frequent SFRP1 methylation in both primary and cultured breast cancer cells (Lo et al, 2006;Veeck et al, 2006). To date, epigenetic silencing of SFRP1 has been identified in a variety of malignancies, including cancers of the bladder (Stoehr et al, 2004), prostate (Lodygin et al, 2005), lung (Fukui et al, 2005) and breast, although abnormalities involving other SFRP family genes are largely unexplored.We previously showed that SFRP1, SFRP2 and SFRP5 are frequently inactivated in CRC and gastric cancer (GC) (Suzuki et al, 2002;Nojima et al, 2007), and that SFRPs suppress constitutive Wnt signalling when overexpressed in CRC and GC cells. Similarly, Bafico et al (2004) reported that constitutive Wnt signalling could be suppressed in breast cancer cells by SFRP1 and DKK1.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Consistent with that idea, we have previously found that SFRP1 is methylated in several breast cancer cell lines (Suzuki et al, 2002), and two other groups recently reported frequent SFRP1 methylation in both primary and cultured breast cancer cells (Lo et al, 2006;Veeck et al, 2006). To date, epigenetic silencing of SFRP1 has been identified in a variety of malignancies, including cancers of the bladder (Stoehr et al, 2004), prostate (Lodygin et al, 2005), lung (Fukui et al, 2005) and breast, although abnormalities involving other SFRP family genes are largely unexplored.We previously showed that SFRP1, SFRP2 and SFRP5 are frequently inactivated in CRC and gastric cancer (GC) (Suzuki et al, 2002;Nojima et al, 2007), and that SFRPs suppress constitutive Wnt signalling when overexpressed in CRC and GC cells. Similarly, Bafico et al (2004) reported that constitutive Wnt signalling could be suppressed in breast cancer cells by SFRP1 and DKK1.…”
supporting
confidence: 72%
“…In addition, two groups recently reported frequent SFRP1 methylation in primary breast tumours (Lo et al, 2006;Veeck et al, 2006), and Bafico et al (2004) clearly demonstrated a novel autocrine mechanism leading to constitutive Wnt signalling in breast cancer, which could be suppressed by SFRP1 and DKK1. Taken together, these results suggest that loss of SFRP1 function is a key mechanism by which Wnt signalling is activated in breast cancer.To date, four SFRP family genes (SFRP1, SFRP2, SFRP4 and SFRP5) and two DKK family genes (DKK1 and DKK3) have been identified as targets of epigenetic silencing in human tumours (Suzuki et al, 2002;Roman-Gomez et al, 2004;Lodygin et al, 2005;Aguilera et al, 2006;Niehrs, 2006). Among them, we showed that loss of SFRP1, SFRP2 and SFRP5 contributes to Wnt signal activation in both CRC and GC.…”
mentioning
confidence: 85%
“…Hence, DKK3 is also known as 'REIC' (Reduced Expression in Immortalized Cells) . Furthermore, DKK3 overexpression suppresses tumor cell growth (Hoang et al, 2004;Abarzua et al, 2005;Lodygin et al, 2005;Kawano et al, 2006). While hypermethylation of human DKK3 correlates with …”
Section: Dkks and Cancermentioning
confidence: 99%
“…Cancer or tumor cell line certain cancers Roman-Gomez et al, 2004;Lodygin et al, 2005), the physiological relevance of altered DKK3 expression in tumors and its potential growth inhibitory effect are unknown. Of note, Dkk3 mutant mice show no enhanced tumorigenesis (del Barco Barrantes et al, 2006).…”
Section: Dkkmentioning
confidence: 99%
“…Initially, significant progress was made by functional epigenomic approaches using gene expression microarrays to study changes in gene expression following global demethylation of cancer cell line genomes (Yamashita et al, 2002;Sato et al, 2003;Lodygin et al, 2005). For RCC, this approach resulted in the identification of B14 candidate RCC TSGs (Morris et al, 2005(Morris et al, , 2010Ibanez de Caceres et al, 2006).…”
Section: Introductionmentioning
confidence: 99%